Impression Of Youngsters In Curup Urban Communities Viewing Pondasi Coffee Shop As A Millennial Way Of Life - Gracia Gabrienda; Mira Yanuarti; Febri Nur Pramudya (Agribusiness Journal, 2024)
Rejang Lebong Regency, as one of the espresso makers in Bengkulu Area, with the potential for very high espresso creation, upholds youthful business people to be imaginative by opening bistros or also called cafés. One of the bistro areas that is very renowned and has a genuinely essential area is the establishment café. Pondasi Coffee Shop has its own appeal, beginning from the inside of the room, to the cost of espresso which is reasonable for youngsters. Establishment Café is overseen by a gathering of millennial youth who can foster their business by really buckling down together, espresso costs start from Rp. 10,000-Rp. ,33,000 with the expectation of complimentary stopping expenses. The establishment bistro gives espresso drinks as well as furnishes snacks with costs beginning from Rp. 10,000-Rp. 15,000 is truly reasonable for the present youngsters. In light of the foundation over, the issue plan in this examination is the impression of youngsters in the city of Curup seeing the Establishment Café as a millennial way of life. This exploration was led at the Pondasi Café in Spring April 2023 at the Pondasi Coffee Shop in Curup City, Rejang Lebong Regency. The information examination utilized in this exploration is Likert scale examination. The inspecting technique utilized was unplanned examining or by chance during the examination time frame so 35 respondents were acquired with an age scope of 18-25 years. The consequences of this examination express that the principal view of guests is Value (X1) with a score of numerous guests picking the concur class with a normal of 3.03, trailed constantly impression of Spot (X3) with a score of numerous guests picking concur classification with a normal of 3.01. Then followed by the third discernment in regards to the Item (X2) with a score of numerous guests deciding to concur with a normal of 3.00 and the last discernment specifically Advancement (X4) with a score of numerous guests deciding to concur with a normal of 2.91 from guest discernments Above, one might say that the four discernments with the most elevated scores are in the "Concur" classification which is regularly picked by guests to the Establishment Café. This can demonstrate that the variables that draw in youngsters to the groundwork of cafés as a millennial way of life are Cost (X1), Spot (X3), Items (X2) and Advancements (X4) which have their own allure for guests beginning from reasonable costs, quality items, delectable preferences, vital areas that are agreeable for guests and with regards to imaginative advancements that increment the interest of guests